GO‐FAANG meeting: a Gathering On Functional Annotation of Animal Genomes. (24th July 2016) - Tuggle, Christopher K.; Giuffra, Elisabetta; White, Stephen N.; Clarke, Laura; Zhou, Huaijun; Ross, Pablo J.; Acloque, Hervé; Reecy, James M.; Archibald, Alan; Bellone, Rebecca R.; Boichard, Michèle; Chamberlain, Amanda; et al.
Summary: The Functional Annotation of Animal Genomes (FAANG) Consortium recently held a Gathering On FAANG (GO‐FAANG) Workshop in Washington, DC on October 7–8, 2015. This consortium is a grass‐roots organization formed to advance the annotation of newly assembled genomes of domesticated and non‐model organisms (www.faang.org ). The workshop gathered together from around the world a group of 100+ genome scientists, administrators, representatives of funding agencies and commodity groups to discuss the latest advancements of the consortium, new perspectives, next steps and implementation plans. The workshop was streamed live and recorded, and all talks, along with speaker slide presentations, are available atwww.faang.org . In this report, we describe the major activities and outcomes of this meeting. We also provide updates on ongoing efforts to implement discussions and decisions taken at GO‐FAANG to guide future FAANG activities. In summary, reference datasets are being established under pilot projects; plans for tissue sets, morphological classification and methods of sample collection for different tissues were organized; and core assays and data and meta‐data analysis standards were established.